The Influence of Firm Size on the ESG Score: Corporate Sustainability Ratings Under Review - Drempetic, Samuel; Klein, Christian; Zwergel, Bernhard (Journal of business ethics, 2020)
The concept of sustainable and responsible (SR) investments expresses that every investment should be based on the SR investor's code of ethics. To a large extent the allocation of SR investments to more sustainable companies and ethical practices is based on the environmental, social, and corporate governance (ESG) scores provided by rating agencies. However, a thorough investigation of ESG scores is a neglected topic in the literature. This paper uses Thomson Reuters ASSET4 ESG ratings to analyze the influence of firm size, a company's available resources for providing ESG data, and the availability of a company's ESG data on the company's sustainability performance. We find a significant positive correlation between the stated variables, which can be explained by organizational legitimacy. The results raise the question of whether the way the ESG score measures corporate sustainability gives an advantage to larger firms with more resources while not providing SR investors with the information needed to make decisions based on their beliefs. Due to our results, SR investors and scholars should reopen the discussion about: what sustainability rating agencies measure with ESG scores, what exactly needs to be measured, and if the sustainable finance community can reach their self-imposed objectives with this measurement.